North and South: The United States, the European Union and the Developing World - Crespo Palomares, Cristina (Universidad de Alcalá. Servicio de Publicaciones, 2013)
This Book compiles a selection of articles from the 6th Transatlantic Studies Conference entitled "North and South: The United States, the European Union and the Developing World", held at Instituto Franklin-UAH (october 20th to 22th, 2011)